2007
DOI: 10.2337/db06-0859
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Lipomatosis Is a Structural Marker in Nondiabetic Children With Mutations in Carboxyl-Ester Lipase

Abstract: Both pancreatic volume reduction and lipomatosis have been observed in subjects with diabetes. The underlying molecular and pathological mechanisms are, however, poorly known, and it has been speculated that both features are secondary to diabetes. We have recently described pancreatic atrophy and lipomatosis in diabetic subjects of two Norwegian families with a novel syndrome of diabetes and exocrine pancreatic dysfunction caused by heterozygous carboxyl-ester lipase (CEL) mutations. To explore the early path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 34 publications
(34 reference statements)
2
60
1
3
Order By: Relevance
“…The latter mechanism may, in addition to glycotoxic cell injury, be one of the explanations why the diabetic subjects had more pancreatic fat than those without diabetes (19,20). Recently, evidence for a possible association between pancreatic lipomatosis and ␤-cell function was demonstrated (22). Using magnetic resonance imaging in 11 nondiabetic nonobese children with heterozygous carboxyl-ester lipase mutation, i.e., a rare mutation that causes diabetes and exocrine pancreatic dysfunction in association with pancreatic lipomatosis in adults, the authors found increased pancreatic fat content and a significant reduction of the first-phase insulin response to intravenous glucose in the mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The latter mechanism may, in addition to glycotoxic cell injury, be one of the explanations why the diabetic subjects had more pancreatic fat than those without diabetes (19,20). Recently, evidence for a possible association between pancreatic lipomatosis and ␤-cell function was demonstrated (22). Using magnetic resonance imaging in 11 nondiabetic nonobese children with heterozygous carboxyl-ester lipase mutation, i.e., a rare mutation that causes diabetes and exocrine pancreatic dysfunction in association with pancreatic lipomatosis in adults, the authors found increased pancreatic fat content and a significant reduction of the first-phase insulin response to intravenous glucose in the mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we expect that more detailed phenotyping using radiological imaging and physiological characterization will improve the value of the registry, enabling us to diagnose monogenic diabetes more efficiently (32). An example is the use of ultrasound examination to diagnose HNF1B-MODY and CEL-MODY (13,33). In the near future, we think tailored hybridization capture for selected genes of interest and very high-coverage sequencing of specific gene panels will replace the traditional Sanger sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Ліпоматоз паренхіми підшлункової залози в носіїв мутації в гені карбоксилестерліпази спостері-гається вже на ранніх стадіях діабету, що пояснює на-явність екзокринної панкреатичної недостатності при синдромі MODY (maturity-onset diabetes of the young -цукровий діабет дорослого типу в молодих). MODY є рідкісною, сімейною, клінічно і генетично гетеро-генною формою діабету, що характеризується почат-ком у молодому віці (як правило, 10-45 років) зі збе-реженням секреції ендогенного інсуліну, із відсутністю автоімунного ураження В-клітин підшлункової залози, відсутністю ожиріння та резистентності до інсуліну з можливістю екстрапанкреатичних проявів [19,20].…”
Section: етіологіяunclassified